2016
DOI: 10.1159/000444534
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Drugs Differentially Affect mRNA Expression of Genes Encoding the Neuregulin 1-Downstream ErbB4-PI3K Pathway

Abstract: Background/Aims: The PIK3CD gene encodes the delta catalytic subunit of phosphoinositide 3-kinase (PI3K), an element of the neuregulin 1-downstream ErbB4-PI3K signaling pathway, which was recently identified as a molecular target for the treatment of schizophrenia. The aim of the study was to examine the effect of haloperidol (HALO), clozapine (CLO), olanzapine (OLA), quetiapine (QUE) and amisulpride (AMI) on the mRNA and protein expression of genes encoding the elements of ErbB4-PI3K pathway, in a human centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
2
14
0
1
Order By: Relevance
“…In the current study, miR-296-5p showed a positive correlation with E-cadherin level, and both in vitro and in vivo experiments also demonstrated that miR-296-5p could reverse the EMT phenotype and metastatic capability in HCC cells. NRG1, a member of NRG family, is known as a key growth factor for the development of the normal nervous system and the occurrence of schizophrenia, which is also involved in cancer progression [ 38 , 39 ]. The relationship between miR-296-5p and NRG1 in HCC was further clarified here.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, miR-296-5p showed a positive correlation with E-cadherin level, and both in vitro and in vivo experiments also demonstrated that miR-296-5p could reverse the EMT phenotype and metastatic capability in HCC cells. NRG1, a member of NRG family, is known as a key growth factor for the development of the normal nervous system and the occurrence of schizophrenia, which is also involved in cancer progression [ 38 , 39 ]. The relationship between miR-296-5p and NRG1 in HCC was further clarified here.…”
Section: Discussionmentioning
confidence: 99%
“…HPRT1, HMBS, RPL13A primer sequences were taken from the work of Vandesompele et al [48]. Integrin and PI3K primer sequences were published elsewhere: ITGA1, ITGA5, ITGA7, ITGA8, ITGA9, ITGA11, ITGAV, ITGB1, ITGB3, ITGB4 [49], ITGA2 [50], ITGA3 [51], ITGA4 [52], ITGAE [53], ITGB2 [54], ITGB5 [55], PIK3CA [56], PIK3CB [57], PIK3CD, PIK3R3 [58], PIK3R1 [59], PIK3R4 [60], PIK3C2B [61]. Other sequences were design using Primer3 software [62] or PrimerBlast [63].…”
Section: Rt-qpcrmentioning
confidence: 99%
“…opposed to AURKA, which was ubiquitously expressed ( Figure 2C, Supplemental Figure 1C, and Supplemental Figure 4D, upper panel). Quantitative reverse transcriptase PCR (qRT-PCR) analysis of PIK3Cδ revealed a similar trend for most of the cell lines tested (Supplemental Figure 4A), though it is well known that protein and mRNA abundances do not always correlate (25,26). Moreover, RNA sequencing (RNA-Seq) in different organs obtained from the Human Protein Atlas (27) revealed that, apart from myeloid and lymphoid cells, fibroblast cell lines express moderate/high PIK3Cδ mRNA levels, in contrast to BC cell lines, which have low/ negligible mRNA transcripts (Supplemental Figure 4B).…”
Section: Cancer-associated Markers In Hmf and Mrc5 Fibroblast Cell LImentioning
confidence: 79%